IMPLEMENTASI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK DI MS GLOW PALEMBANG - Tiara Maharani; Nuraida Nuraida; Dalinur Muhammad Nur; Hasril Atieq Pohan (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
The increasing development of technology has an impact on all lines of people's lives. This also has an impact on the marketing system in various companies and various other business fields, MS Glow Palembang is one that utilizes technological developments in the interests of digital marketing. This research is entitled Implementation of Digital Marketing in Increasing Product Sales at MS Glow Palembang. This study aims to determine the digital marketing media used, the level of sales, and the implementation of digital marketing by MS Glow Palembang in increasing product sales. This research is a field research with qualitative methods, in collecting data the researchers used the methods of observation, interviews, and documentation. The focus of the research is the use of the WhatsApp application as a liaison between sellers and potential consumers based on digital marketing theory, namely interactive, incentive programs, site design, and transactions. This research resulted in: 1). The level of sales at MS Glow Palembang remained stable even though during the pandemic there were no visitors to the store (stores), because sales focused on online or digital systems. 2). Digital marketing at MS Glow Palembang uses several trending social media such as Instagram, Tiktok, and WhatsApp, as well as using the e-commerce application, Shopee. 3). Implementation of digital marketing in increasing product sales at MS Glow Palembang, by utilizing various existing features to make it easier to build persuasive interactions with potential customers and build better relationships by providing past response services, as well as providing educative and informative content on a regular basis or regularly every day. Meanwhile, at the level of sales, MS Glow Palembang provides save, free and win as an effort to attract consumer buying interest which has a positive impact on sales. Keywords: Digital Marketing, Sales Level, MS Glow Palembang